PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN WEDDING PACKAGE DI SIX SENSES ULUWATU, BALI - Oola, Sarako Ritnama; Kalpikawati, Ida Ayu; Wiartha, Nyoman Gede Mas (Program Studi Administrasi Perhotelan, 2024)
Brand image and price are key factors that influence purchasing decisions, especially in the competitive wedding service industry. This study aims to examine the effect of brand image and price on purchasing decisions for wedding packages at Six Senses Uluwatu, Bali. A quantitative approach was used with a saturated sampling technique, involving 75 respondents who had purchased wedding packages at the venue. Data were collected through questionnaires and analyzed using Multiple Linear Regression, Coefficient of Determination, t-test, and F-test. The results show that both brand image and price have a positive and significant impact on purchasing decisions, both individually and simultaneously. The combined contribution of brand image and price to the purchasing decision is 69.3%, while the remaining 30.7% is influenced by other factors not examined in this study, such as service quality, product quality, and promotional efforts. The findings suggest that maintaining a strong brand image and offering competitive pricing are crucial strategies for attracting consumers in the luxury wedding market.